Staphylococcus epidermidis Sensitizes Perinatal Hypoxic-Ischemic Brain Injury in Male but Not Female Mice - Gravina, Giacomo; Svedin, Pernilla; Ardalan, Maryam; Levy, Ofer; Ek, C. Joakim; Mallard, Carina; Lai, Jacqueline C. Y. (Frontiers in Immunology, 2020)
Staphylococcus epidermidis is the most common nosocomial infection and the predominant pathogen in late onset sepsis in preterm infants. In preterm infants, perinatal infection and inflammation is linked to subsequent neurological and developmental sequelae. Several findings also suggest that bacterial infections can increase the vulnerability of the developing brain to hypoxia-ischemia (HI). We tested the hypothesis that S. epidermidis exacerbates neuropathology associated with HI in neonatal mice. Methods: Male and female C57Bl/6 mice were injected intraperitoneally with sterile saline or 3.5×107 colony-forming units of S. epidermidis on postnatal day (PND) 4. On PND5 (24 h after injection) or PND9 (5 d after injection) plasma, brain and liver were collected to evaluate cytokine and chemokine profiles using multiplex cytometric bead arrays, detection of C5a levels with ELISA and C5 signalling with qPCR. An additional group of animals was injected on PND4 and then subjected to HI on PND5 or PND9 by left carotid artery ligation and exposure to 10% O2. Brains were collected at PND14-16 for the assessment of white and grey matter injury. Results: HI induced 24 h after injection of S. epidermidis resulted in greater grey and white matter tissue loss in males, but not in females. Specifically, in males, we observed an increase of grey matter tissue loss in the cortex and striatum, and in subcortical white matter, hippocampal fimbria and white matter of the striatum. In contrast, there was no potentiation of brain injury when HI occurred 5 d after S. epidermidis infection in either sex. In plasma, S. epidermidis-injected mice demonstrated increased pro- and anti-inflammatory cytokines and chemokines levels and a reduction of C5a 24 h, but not 5 d, after infection. Brain CCL levels were increased in both sexes 24 h after infection, but only in males at 5 d. Conclusion: Ongoing S. epidermidis infection combined with neonatal HI increases the vulnerability of the developing brain in male but not in female mice. These sex-dependent effects were to a large extent independent of expression of systemic cytokines or brain CCL2. Overall, we provide new insights into how systemic S. epidermidis infection affects the developing brain.